Multiplicative interaction of functional inflammasome genetic variants in determining the risk of gout. Issue 1 (December 2015) - McKinney, Cushla; Stamp, Lisa; Dalbeth, Nicola; Topless, Ruth; Day, Richard; Kannangara, Diluk; Williams, Kenneth; Janssen, Matthijs; Jansen, Timothy; Joosten, Leo; Radstake, Timothy; Riches, Philip; et al.
Abstract Introduction The acute gout flare results from a localised self-limiting innate immune response to monosodium urate (MSU) crystals deposited in joints in hyperuricaemic individuals. Activation of the caspase recruitment domain-containing protein 8 (CARD8) NOD-like receptor pyrin-containing 3 (NLRP3) inflammasome by MSU crystals and production of mature interleukin-1β (IL-1β) is central to acute gouty arthritis. However very little is known about genetic control of the innate immune response involved in acute gouty arthritis. Therefore our aim was to test functional single nucleotide polymorphism (SNP) variants in the toll-like receptor (TLR)-inflammasome-IL-1β axis for association with gout. Methods 1, 494 gout cases of European and 863 gout cases of New Zealand (NZ) Polynesian (Māori and Pacific Island) ancestry were included. Gout was diagnosed by the 1977 ARA gout classification criteria. There were 1, 030 Polynesian controls and 10, 942 European controls including from the publicly-available Atherosclerosis Risk in Communities (ARIC) and Framingham Heart (FHS) studies. The ten SNPs were either genotyped by Sequenom MassArray or by Affymetrix SNP array or imputed in the ARIC and FHS datasets. Allelic association was done by logistic regression adjusting by age and sex with European and Polynesian data combined by meta-analysis. Sample sets were pooled for multiplicative interaction analysis, which was also adjusted by sample set. Results Eleven SNPs were tested in theTLR2, CD14, IL1B, CARD8, NLRP3, MYD88, P2RX7, DAPK1 andTNXIP genes. Nominally significant (P  < 0.05) associations with gout were detected atCARD8 rs2043211 (OR = 1.12, P =  0.007), IL1B rs1143623 (OR = 1.10, P  = 0.020) andCD14 rs2569190 (OR = 1.08;P  = 0.036). There was significant multiplicative interaction betweenCARD8 andIL1B (P  = 0.005), with theIL1B risk genotype amplifying the risk effect ofCARD8. Conclusion There is evidence for association of gout with functional variants inCARD8, IL1B andCD14 . The gout-associated allele ofIL1B increases expression of IL-1β – the multiplicative interaction withCARD8 would be consistent with a synergy of greater inflammasome activity (resulting from reduced CARD8) combined with higher levels of pre-IL-1β expression leading to increased production of mature IL-1β in gout.